Rhymes and Riddles with Corduroy - Freeman, Don; McCue, Lisa. (New York, 2002)
A collection of rhyming riddles about what's special in every month of the year, featuring Corduroy the teddy bear.
Keywords: Months; Fiction; Teddy bears; Fiction; Riddles; Stories in rhyme